A hierarchical microstructure due to chemical ordering in the bcc lattice: Early stages of formation in a ferritic Fe–Al–Cr–Ni–Ti alloy. (15th June 2015) - Liebscher, C.H.; Radmilović, V.R.; Dahmen, U.; Vo, N.Q.; Dunand, D.C.; Asta, M.; Ghosh, G.
Graphical abstract: Abstract: A hierarchical microstructure is obtained in an alloy with composition Fe–8.1Al–12.2Cr–1.9Mo–18.2Ni–2.0Ti (wt.%) processed by melt-spinning. The evolution of the precipitation pathways is investigated using transmission electron microscopy (TEM) techniques, atom probe tomography (APT) and first-principles thermodynamic calculations. As-solidified ribbons exhibit a random dispersion of B2-ordered precipitates (NiAl-type) in an Fe-based matrix. Subsequent aging at 700 °C yields nucleation and growth of the L21 -phase (Ni2 TiAl-type) within the primary B2-precipitates, leading to a microstructure exhibiting three types of hierarchy: (i) a structural hierarchy due to chemical ordering, with a chemically disordered matrix of bcc-Fe (A2), the nearest-neighbor (NN) ordered B2-precipitates (NiAl-type) and the next nearest-neighbor (NNN) ordered L21 -precipitates (Ni2 TiAl-type) within B2, (ii) a dimensional hierarchy with a continuous bcc-Fe matrix, coherently embedded B2-precipitates, with a size range of 60–200 nm and the coherent precipitate substructure, with L21 -phase and dimensions of 15–20 nm. (iii) A spatial hierarchy where B2-precipitates are embedded in the bcc-Fe matrix and L21 -precipitates nucleate and grow only within B2-precipitates. In addition, it is verified that the interface between B2 and L21 is coherent and adopts a diffuse structural profile. Monte-Carlo simulations reproduce these observations and it is found that interface energies of B2 and L21 reduce from 50 mJ/m 2 at 0 K to 11 mJ/m 2 at 973 K. Kinetic-Monte-Carlo simulations support the interpretation of the experimental results that the L21 nucleates within the B2 phase.